Factors Influencing Purchase Behavior through TikTok Live Commerce among Generation Z Consumers in Thailand - สุขสวัสดิ์, เรณุกา; ฐานิตธนกร, นิตนา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study is motivated by the rapid growth of TikTok Live Commerce, which significantly influences the purchasing behavior of Generation Z consumers in Thailand. The objective is to examine factors affecting purchase behavior, including logistics service quality, platform stability, opinion leadership, parasocial interaction, trust in live streamers, and purchase convenience. A quantitative approach was employed, with data collected from 253 Generation Z consumers in Thailand who have purchased products via TikTok Live Commerce using structured questionnaires. Multiple regression analysis was conducted. The results indicate that parasocial interaction and trust in live streamers have the strongest influence on purchase behavior, followed by platform stability and opinion leadership. In contrast, logistics service quality and purchase convenience have no statistically significant effect. These findings highlight the importance of building trust and relationships between live streamers and consumers to effectively influence purchase decisions.